Sustaintability in practice: The reality of environmental education in a São Paulo state school - Ohi, Ana Gabriela Kolde; Ganiko-Dutra, Matheus (Revista Hipótese, 2023)
STSE (Science, Technology, Society, and Environment) Education proposes a teaching approach in which students can participate in decision-making processes related to these subjects. This approach is influenced by Environmental Education (EE) branches, which, in turn, are connected to existing sustainability models. In this supervised internship conducted as a research project, the relationship between a public school in the interior of São Paulo state and sustainability models was investigated. Classroom observations, school analysis, and library book analysis were conducted. It was possible to identify the adoption of Standard Sustainable Development and Neocapitalist Models by the school, which are related to the sustainability branch of EE. It was found that the teacher's knowledge of the various aspects of EE allows for selecting branches that align most closely with the STSE proposal.
Keywords: School library; Science Education; Initial teacher education